2017
DOI: 10.1037/abn0000308
|View full text |Cite
|
Sign up to set email alerts
|

A method for making inferences in network analysis: Comment on Forbes, Wright, Markon, and Krueger (2017).

Abstract: Forbes, Wright, Markon, and Krueger (2017) make a compelling case for proceeding cautiously with respect to the overinterpretation and dissemination of results using the increasingly popular approach of creating “networks” from co-occurrences of psychopathology symptoms. We commend the authors on their initial investigation and their utilization of cross-validation techniques in an effort to capture the stability of a variety of network estimation methods. Such techniques get at the heart of establishing “repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 33 publications
1
73
0
Order By: Relevance
“…Moreover, concerns have recently been raised that network analyses have limited replicability (Forbes, Wright, Markon, & Kreuger, ; though see Borsboom et al, ; Epskamp, Borsboom, & Fried, ). In fact, two research groups concluded that current network estimation methods produce unreliable results with “poor and absent replicability” (Forbes et al, , p. 981; Steinley, Hoffman, Brusco, & Sher, ). These critiques highlight the need for high‐quality ED network replication studies, as unique characteristics about published ED networks raise replicability concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, concerns have recently been raised that network analyses have limited replicability (Forbes, Wright, Markon, & Kreuger, ; though see Borsboom et al, ; Epskamp, Borsboom, & Fried, ). In fact, two research groups concluded that current network estimation methods produce unreliable results with “poor and absent replicability” (Forbes et al, , p. 981; Steinley, Hoffman, Brusco, & Sher, ). These critiques highlight the need for high‐quality ED network replication studies, as unique characteristics about published ED networks raise replicability concerns.…”
Section: Introductionmentioning
confidence: 99%
“…While network theory (e.g., Borsboom, 2017) calls attention to interesting and potentially important avenues for future research, the current psychopathology network methodologies are plagued with substantial flaws. For example, in the few months since our target article was accepted for publication, a series of papers have emerged on substantial problems facing the methods, in addition to poor replicability (Bos et al, 2017;Epskamp et al, 2017;Fried & Cramer, in press;Guloksuz, Pries & van Os, 2017;Steinley et al, 2017;Wichers, Wigman, Bringmann & de Jonge, 2017). Taken together, this growing literature highlights the remarkable sensitivity of psychopathology network results to a multitude of factors including the study design, variables included, characteristics of the data, and analytic methods (e.g., Bulteel, Tuerlinckx, Brose & Ceulemans, 2016;Terluin, de Boer & de Vet, 2016;Wichers et al, 2017).…”
Section: The Future Of Psychopathology Networkmentioning
confidence: 99%
“…The two commentaries on our target article (Forbes, Wright, Markon, & Krueger, 2017), from advocates of psychopathology networks and scholars versed in multivariate statistical methodology (Steinley, Hoffman, Brusco & Sher, 2017) differ substantially in their assessment of our findings. Borsboom et al question the accuracy and validity of our work, and present a re-analysis of the data that they suggest provides evidence that "network models replicate very well" (p. 3).…”
Section: Introductionmentioning
confidence: 97%
“…Steinley, Hoffman, Brusco, & Sher, 2017). Much of the research on the latent structure of psychopathology relies on dichotomous diagnosis-level data.…”
mentioning
confidence: 99%
“…As with other binary data analysis contexts, measures of association among diagnoses are sensitive to base rates, which vary widely across community, outpatient, and inpatient settings; for example, relationships between binary disorders are often highly inflated by noncases because of the low prevalence of disorders in unselected, community-based samples (cf. Steinley, Hoffman, Brusco, & Sher, 2017).…”
mentioning
confidence: 99%